2022
DOI: 10.1002/adtp.202200027
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared Light‐Activatable Bismuth‐Based Nanomaterials for Antibacterial and Antitumor Treatment

Abstract: The treatment of diseases through precision phototherapy has attracted growing interest during the last decade. Remarkably, biocompatible bismuth‐based nanomaterials can be effectively activated by near‐infrared (NIR) light to fight bacterial infections and tumors. In addition, bismuth‐containing nanostructures are easy to be synthesized and exhibit excellent NIR absorption, ideal photothermal conversion, and X‐ray sensitivity for diagnosis and treatment. This review outlined the recent development of bismuth‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 115 publications
(158 reference statements)
0
6
0
Order By: Relevance
“…In the past decades, advanced functional nanomaterial-based antitumor strategies have shown great potential in achieving DOI: 10.1002/adma.202302559 remarkable antitumor effects by overcoming the bottleneck in traditional treatments. [7][8][9] For instance, the enhanced therapeutic efficacy and reduced side effects of chemotherapy can be achieved with the employment of tumor-targeting or tumorresponsive release nanocarriers. [10][11][12] For spatiotemporal controllable photothermal therapy (PTT), an increasing number of nanomaterials with high photothermal conversion efficiency have been developed to realize the gratifying antitumor effects.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, advanced functional nanomaterial-based antitumor strategies have shown great potential in achieving DOI: 10.1002/adma.202302559 remarkable antitumor effects by overcoming the bottleneck in traditional treatments. [7][8][9] For instance, the enhanced therapeutic efficacy and reduced side effects of chemotherapy can be achieved with the employment of tumor-targeting or tumorresponsive release nanocarriers. [10][11][12] For spatiotemporal controllable photothermal therapy (PTT), an increasing number of nanomaterials with high photothermal conversion efficiency have been developed to realize the gratifying antitumor effects.…”
Section: Introductionmentioning
confidence: 99%
“…However, the low electron mobility and rapid hole-electron recombination give rise to a low ROS production capability of these reported Bi 2 S 3 NMs. Intriguingly, the photodynamic performance of Bi 2 S 3 NMs can be significantly improved by forming heterostructures especially Z-scheme heterostructures with other materials [16] . Z-scheme heterostructure materials which are composed of two different semiconductors (PS I and PS II) and solid electronic mediator, not only effectively achieve the spatial separation of electron-hole pairs, but also remain the strong oxidation–reduction active sites, directly leading to the improved efficiency of ROS generation under irradiation [17] .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Bi nanostructures have drawn extensive attention due to their fascinating properties, such as a high surface area, easy functionalization, narrow bandgap, high X-ray attenuation coefficient, low toxicity, and high stability [ 30 , 31 , 32 , 33 ]. It was demonstrated that Bi nanostructures, such as Bi nanoparticles (NPs) [ 34 ], and mesoporous silica supported Ag-Bi NPs [ 35 , 36 ], exhibited superior antibacterial performance without antibiotics due to their facile controllability, poor drug resistance, and negligible side effects. The above-mentioned features merit Bi nanostructures as ideal candidates for cost-efficient, stable, and non-toxic antibacterial agents.…”
Section: Introductionmentioning
confidence: 99%